2016
DOI: 10.1155/2016/6123268
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Phase Transform Behavior in Indium Selenide Based RAM and Its Validation as a Memory Element

Abstract: Phase transform properties of Indium Selenide (In2Se3) based Random Access Memory (RAM) have been explored in this paper. Phase change random access memory (PCRAM) is an attractive solid-state nonvolatile memory that possesses potential to meet various current technology demands of memory design. Already reported PCRAM models are mainly based upon Germanium-Antimony-Tellurium (Ge2Sb2Te5 or GST) materials as their prime constituents. However, PCRAM using GST material lacks some important memory attributes requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[46][47][48][49][50][51] Moreover, experiments have revealed that the "priming" of crystalline nuclei in the amorphous state, which is denoted as the primed state, can lead to ultra-rapid set (crystallization) operations. [52][53][54] The primed state can be distinguished from the amorphous state with regard to their altered responses to thermal or electric stimuli, although a negligible variation occurs in the electrical conductance. The partially-crystallized states have also been harnessed for brain-inspired neuromorphic applications, where multilevel set transitions were utilized.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49][50][51] Moreover, experiments have revealed that the "priming" of crystalline nuclei in the amorphous state, which is denoted as the primed state, can lead to ultra-rapid set (crystallization) operations. [52][53][54] The primed state can be distinguished from the amorphous state with regard to their altered responses to thermal or electric stimuli, although a negligible variation occurs in the electrical conductance. The partially-crystallized states have also been harnessed for brain-inspired neuromorphic applications, where multilevel set transitions were utilized.…”
Section: Resultsmentioning
confidence: 99%